Sustainable corporate governance – nový trend v obchodním právu - Lucie Josková (Acta Universitatis Carolinae. Iuridica)
The issue of sustainability (both in relation to the environment and in relation to human rights) has long been considered the domain of public law or selected private law disciplines. In recent decades, there has been an effort to reverse this trend and to use other areas of private law, including business law, to achieve sustainability. This corresponds to the fact that sustainability has become a major issue of the 21st century and its achievement a global challenge; thus, the effort to use any effective tools seems logical. In business law, sustainability is reflected in a number of areas (e.g., due diligence in supply chains or the issue of greenwashing), but most intimately in the internal governance of business corporations; in this context, we speak of sustainable corporate governance. Although this term is often mentioned in literature and practice, its definition is unclear. The aim of this paper is to define the concept of sustainable corporate governance and its place in corporate law, and to briefly introduce and sort out the instruments that are intended to help achieve sustainable corporate governance.